Analisa Kerusakan Komponen Differential Unit Wheel Loader 914 G Caterpillar - Abdul Halim; Abdul Halik; Hidayat Hidayat; Baso Cante; Yudi Sukmono (Politeknik Negeri Samarinda, 2022)
Wheel loader is one of the heavy equipment units used to move materials. One of the parts of concern for the machine unit is the differential which functions to move the rotational power from the propeller shaft to the rear wheel axle. This study aims to find the cause of damage to the differential components of Caterpillar's 914G unit. The method used is library research which begins with taking data from the Service Information System (SIS) as standard data and various modules related to the object of research, field observation by disassembling, visual inspection of objects, and ending with measurements that will be compared with standard data. The results of this study showed that measurements on the backlash component between the bevel gear and pinion shaft were 0.31 mm with standard specifications of 0.18-0.36 mm (in spec), damage to the ring gear due to contact stress fatigue wear, scratches due to abrasives on the side gear, and there was spider gear damage due to contact stress fatigue wear.